How to Rethink and Redefine the Terminology of the Concept of Spectator in Contemporary Times - Zabolinezhad, Hoda (Journal of Ecohumanism, 2023)
This reflection aims to rethink and redefine the notion of the spectator in the context of the contemporary era. To address this issue, we draw upon Christian Ruby’s hypotheses concerning the characteristics of today’s spectator, as well as Arthur Danto’s hypotheses regarding the role and place of the spectator in the reception process, considered an indispensable complement to artistic creation. Through an in-depth analysis of RUSKIN and GREENBERG’S theory of the "innocent eye," and Roger POUIVET ’s theory of "applied ontology" —which is rooted in a pragmatist approach that considers each work as a unique entity, independent of any prior ontological reference—this reflection highlights a forward-thinking conception of the reception of artworks in the contemporary context.As this analysis unfolds, it becomes clear that the methodology adopted is analytical in nature and that the collection of information relies primarily on bibliographic research. It emerges that the viewer always remains free to interpret and determine the meaning of a work of art. In fact, it is the viewer who completes the process: once the work is exhibited, the artist no longer exercises any control over how it will be received and understood by viewers.